Biodiesel from oleaginous microbes: opportunities and challenges. Issue 1 (2nd January 2019) - Gujjala, Lohit K. S.; Kumar, S. P. Jeevan; Talukdar, Bitasta; Dash, Archana; Kumar, Sanjeev; Sherpa, Knawang Ch.; Banerjee, Rintu
ABSTRACT: The quest for renewable and alternative sources of energy is a pressing demand of the 21 st century considering the rapid escalation in demand owing to the rising population. Biodiesel is one of the favorite candidates that many scientists, investors, policymakers, etc. are banking upon for fulfilling it's demand. Production of biodiesel from plant sources has long been researched, but with the rising population there is an added issue of the food vs. fuel controversy, which jeopardizes this source as an option. Considering this background, microbial sources for biodiesel production, viz. oleaginous yeasts, fungi and microalgae, are perfect candidates, which can serve the purpose of fulfilling the energy demand while avoiding the food vs. fuel controversy. In this review article, a comprehensive viewpoint of lipid production from various microbial sources is discussed, with major emphasis on understanding the biochemistry of lipid accumulation, along with the biosynthesis of fatty acids and triacylglycerides, which comprise the majority of the lipids. Emphasis is placed on highlighting the different biochemical and metabolic strategies adopted to improve lipid yields. Finally, a comparison is drawn between the biodiesel produced from algal and yeast sources.